Glycated Lysine Residues: A Marker for Non-Enzymatic Protein Glycation in Age-Related Diseases. Issue 6 (28th May 2013) - Ansari, Nadeem A.; Moinuddin,; Ali, Rashid
Abstract : Nonenzymatic glycosylation or glycation of macromolecules, especially proteins leading to their oxidation, play an important role in diseases. Glycation of proteins primarily results in the formation of an early stage and stable Amadori-lysine product which undergo further irreversible chemical reactions to form advanced glycation endproducts (AGEs). This review focuses these products in lysine rich proteins such as collagen and human serum albumin for their role in aging and age-related diseases. Antigenic characteristics of glycated lysine residues in proteins together with the presence of serum autoantibodies to the glycated lysine products and lysine-rich proteins in diabetes and arthritis patients indicates that these modified lysine residues may be a novel biomarker for protein glycation in aging and age-related diseases.